Delayed union of a surgically treated fragility fracture of the pelvis: A case report. (2020) - Yanagisawa, Yohei; Matsumoto, Yukei; Hoshino, Tetsuya; Inoue, Yoshiaki; Yamazaki, Masashi
Highlights: A case of delayed union of type IIIa fragility fracture of the pelvis. Evaluating the progress of bone fusion may be difficult using front and side X-rays. This may be because of the implant position and pelvis shape. CT enables diagnosis of delayed union and non-union in type IIIa pelvis fracture. Abstract: INTRODUCTION: There are no universally accepted treatment strategies for fragility fractures of the pelvis (FFPs). The incidence of delayed union or non-union of Type IIIa FFP is still unknown. PRESENTATION OF CASE: We describe a case of delayed union of a Type IIIa FFP. A 96-year-old female patient who lives independently accidentally fell when exiting a car. The diagnosis of Type IIIa FFP with displaced left ilium and left pubic rami fracture. Surgical repair was performed using an anterior intrapelvic approach with constructs made using two reconstruction contoured plates to bridge the medial edge and middle part of the fracture. This case was revealed delayed union. The periodic CT examinations were performed to determine the progress of bone union. The patient returned to most social activities including living independently and the Modified Majeed score was 94 at 12 months post-operation. DISCUSSION: For the case of TypeⅢa FFP, soft tissue is spread over a wide area. When the fracture site of ilium was exposed, the cortical bone was found to be thin with poor blood flow. There is a possibility that the blood flow was hindered by subperiosteal elevation of the iliacus muscle from the internal iliac fossa in this case. CONCLUSION: Non-union of the iliac wings is relatively rare following high-energy pelvic ring fractures. The incidence of delayed union or non-union of Type IIIa FFP remains unknown; therefore, careful follow-up of patients who undergo treatment is necessary to reduce the risk of delayed union.